2001
DOI: 10.1002/j.2168-9830.2001.tb00575.x
|View full text |Cite
|
Sign up to set email alerts
|

Making Engineering Education Fun

Abstract: Maintaining student interest is more than an academic exercise. Institutions or departments that fail to challenge and actively involve their students in the learning process risk losing them to competing programs where the curricula are more dynamic and relevant. Within the Department of Nuclear Engineering at Oregon State University, we continually seek innovative ways to promote student retention while maintaining academic excellence. One recent effort was to restructure a first-year nuclear engineering/hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 3 publications
0
35
0
Order By: Relevance
“…The online e-quiz was based on Socrative (Méndez, Slisko 2013). However, the e-quiz was not summatively assessed, as it was intended to have students to undergo learning with fun (Higley, Marianno 2001). Thus, after a question was answered within the e-quiz assessment, each student's name as well as the answer (s)he has given was displayed on the projector screen, thus the student was expected to answer with fun (courtesy no marking) but also had to be serious (courtesy projector displaying everyone's answer).…”
Section: A Laying the Foundationsmentioning
confidence: 99%
“…The online e-quiz was based on Socrative (Méndez, Slisko 2013). However, the e-quiz was not summatively assessed, as it was intended to have students to undergo learning with fun (Higley, Marianno 2001). Thus, after a question was answered within the e-quiz assessment, each student's name as well as the answer (s)he has given was displayed on the projector screen, thus the student was expected to answer with fun (courtesy no marking) but also had to be serious (courtesy projector displaying everyone's answer).…”
Section: A Laying the Foundationsmentioning
confidence: 99%
“…Examples are murder mysteries (Highley & Marianno, 2001) or river crossing (Michaelewicz & Michaelewicz, 2007;Moursund, 2007). Moursund (2007) argues that it is up to the students to make the connection between the constructed examples and the real world.…”
Section: "Fun Task; As It Is From Real Life"mentioning
confidence: 99%
“…Previous research has shown that there must be rules in order to solve the puzzle (Highley & Marianno, 2001). In our case, the students were not allowed to search the Internet, and they were informed about these rules in advance.…”
Section: "Very Good To Learn How This Information Can Be Used To Makementioning
confidence: 99%
“…The numbers given to the mentioned statements, as well as the observation of the Author during the Project, verify the high level of teamwork in an enjoyable active environment. Such environment in engineering education would increase the level of understanding of the participants, as well as the retention rate 17 . Incidentally, having background information about the participants facilitates more in depth data analysis.…”
Section: Discussionmentioning
confidence: 99%
“…However, Ji and Bell claim that engineering students show a greater interest in topics which are demonstrated physically, than in topics that are explained using the so called 'chalk and talk' method, that is, by oral presentation and blackboard/whiteboard/OHP 4 . Also, the students are motivated by hands-on experience and by linking concepts and models to real engineering problems 4,17 . Hands-on activities have been implemented not only in engineering education but also in provisional programmes of the Science, Technology, Engineering and Mathematics (STEM) fields.…”
Section: Literature Reviewmentioning
confidence: 99%